Relationship Between Nutritional Status and Work Posture with Work Fatigue on Crane Operators - Andhini Aurelia Putri; Maulid Diaturrochma; Andika Savira Putri; Endang Dwiyanti (The Indonesian Journal of Occupational Safety and Health, 2022)
Introduction: Work accidents can occur due to two factors, namely unsafe human behavior and unsafe environmental conditions. One of the unsafe human behavior is work fatigue. In addition, work fatigue can also reduce productivity so that it can have a bad impact on the company. This study aims to determine the strength of the relationship and the direction of the correlation between nutritional status and work postures with work fatigue on crane operators. Method: This research is included in the type of descriptive observational research with a cross-sectional approach. The sample of this study was taken using total sampling, namely all the population of 30 people. The independent variables in this study were nutritional status and body postures, while the dependent variable was work fatigue. The data were analyzed using the Spearman's correlation coefficient (Spearman rank's correlation coefficient) to see the value of the correlation coefficient. Results: The correlation coefficient between nutritional status and work fatigue was -0.169, which means there was a very weak relationship with a negative direction. Meanwhile, the strength of the relationship between work postures and work fatigue can be seen in the correlation coefficient of 0.671, which means there was a strong relationship with a positive direction. Conclusion: Workers with overweight and obese nutritional status wwere more relaxed at work and did not pursue daily targets so that the fatigue experienced was classified as moderate. In addition, poor work postures can cause severe work fatigue.